(untitled) (Journal of Economic Research & Business Administration, 2015)
Today the priorities in agriculture development were distributed as follows: land relations development, the efficient systems generating of agricultural water competence, optimization of the sowing areas structure, plants protection and quarantine, development of livestock breeding and veterinary medicine, development of agricultural engineering, insurance, crediting and tax policy. It’s also necessary to reform and develop marketing information system for the successful reforms.